Progress and prospects of biomarker-based targeted therapy and immune checkpoint inhibitors in advanced gastric cancer - Zeng, Zhu; Zhu, Qing (Frontiers in Oncology, 2024)
Gastric cancer and gastroesophageal junction cancer represents the leading cause of tumor-related death worldwide. Although advances in immunotherapy and molecular-targeted therapy have expanded treatment options, they have not significantly altered the prognosis for patients with unresectable or metastatic gastric cancer. A minority of patients, particularly those with PD-L1positive, HER-2-positive, or MSI-high tumors, may benefit more from immune checkpoint inhibitors and/or HER-2-directed therapies in advanced stages. But for those lacking specific targets and unique molecular features, conventional chemotherapy remains the only recommended effective and durable regimen. In this review, we summarize the roles of various signaling pathways and further investigate the available targets. Then, the current results of phase II/ III clinical trials in advanced gastric cancer, along with the superiorities and limitations of the existing biomarkers, are specifically discussed. Finally, we will offer our insights in precision treatment pattern when encountering the substantial challenges.